Acute Corneal Toxicity of Combined Antiglaucoma Topical Eyedrops. (2nd October 2016) - Mohamed, Yasser Helmy; Uematsu, Masafumi; Onizuka, Naoko; Ueki, Ryotaro; Inoue, Daisuke; Fujikawa, Azusa; Sasaki, Hitoshi; Kitaoka, Takashi
ABSTRACT: Purpose : To investigate the corneal toxicity of three combined antiglaucoma topical eyedrops using transepithelial electrical resistance (TER) and scanning electron microscopy (SEM). Methods : Corneal TER changes after a 60-s exposure to latanoprost/timolol with 0.02% benzalkonium chloride (BAC), travoprost/timolol with polyquaternium-1, and dorzolamide/timolol with 0.005% BAC were measured in living rabbits. Corneal damage was also examined by SEM. Hank's balanced salt solution (HBSS) was used as a control. Results : There was a significant decrease in the corneal TER after exposure of the cornea to latanoprost/timolol with 0.02% BAC. Travoprost/timolol with polyquaternium-1 and dorzolamide/timolol with 0.005% BAC did not produce any significant decrease in the corneal TER as compared to HBSS control eyes. SEM revealed that superficial cells of corneas treated with latanoprost/timolol with 0.02% BAC were damaged and exhibited degenerated microvilli. Conversely, the superficial cells of corneas exposed to travoprost/timolol with polyquaternium-1 or dorzolamide/timolol with 0.005% BAC appeared normal and had normal microvilli under SEM examinations. Conclusion : The corneal toxicity of latanoprost/timolol with 0.02% BAC is greater than that of travoprost/timolol with polyquaternium-1 and dorzolamide/timolol with 0.005% BAC. Latanoprost/timolol contains 0.02% BAC, which may be responsible for the corneal toxicity.